Economic evaluation of the introduction of rotavirus vaccine in Hong Kong. Issue 1 (3rd January 2021) - Yeung, Karene Hoi Ting; Lin, Shi Lin; Clark, Andrew; McGhee, Sarah M.; Janusz, Cara Bess; Atherly, Deborah; Chan, Kate C.; Nelson, E. Anthony S.
Abstract: Background: Rotavirus is a common cause of severe gastroenteritis in young children in Hong Kong (HK) with a high economic burden. This study aimed to evaluate the cost-effectiveness of introducing rotavirus vaccination into the HK Government's Childhood Immunisation Programme (CIP) and to include the potential protective effect of the vaccine against seizures. Methods: A decision-support model was customised to estimate the potential impact, cost-effectiveness and benefit-risk of rotavirus vaccination in children below 5 years over the period 2020–2029 in HK. Two doses of Rotarix® and three doses of RotaTeq® were each compared to no vaccination. Rotavirus treatment costs were calculated from a governmental health sector perspective (i.e., costs of public sector treatment) and an overall health sector perspective (both governmental and patient, i.e., costs of public sector treatment, private sector treatment, transport and diapers). We ran probabilistic and deterministic uncertainty analyses. Results: Introduction of rotavirus vaccination in HK could prevent 49, 000 (95% uncertainty interval: ~44, 000–54, 000) hospitalisations of rotavirus gastroenteritis and seizures and result in ~50 (95% uncertainty interval: ~25–85) intussusception hospitalisations, over the period 2020–2029 (a benefit-risk ratio of ~1000:1), compared to a scenario with no public or private sector vaccine use. The discounted vaccination cost would be US$51–57 million over the period 2020–2029 based on per-course prices of US$72 ( Rotarix®) or US$78 ( RotaTeq® ), but this would be offset by discounted treatment cost savings of US$70 million (government) and US$127 million (governmental and patient health sector). There was a greater than 94% probability that the vaccine could be cost-saving irrespective of the vaccine product or perspective considered. All deterministic 'what-if' scenarios were cost-saving from an overall health sector perspective (governmental and patient). Conclusions: Rotavirus vaccination is likely to be cost-saving and have a favourable benefit-risk profile in HK. Based on the assumptions made, our analysis supports its introduction into CIP.